2023
DOI: 10.1002/ijgo.14626
|View full text |Cite
|
Sign up to set email alerts
|

Effects on heavy menstrual bleeding and pregnancy of uterine artery embolization (UAE) or myomectomy for women with uterine fibroids wishing to avoid hysterectomy: The FEMME randomized controlled trial

Abstract: Objective To determine treatment options (myomectomy vs. uterine artery embolization (UAE)) for women wishing to avoid hysterectomy. Methods A multicenter randomized controlled trial was conducted on 254 women and data were collected on fibroid‐specific quality of life (UFS‐QOL), loss of menstrual blood, and pregnancy. Results At 4 years, the mean difference in the UFS‐QOL was 5.0 points (95% confidence interval (CI) −1.4 to 11.5; P = 0.13) in favor of myomectomy. This was not statistically significant as it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…However, since the side effects that develop during treatment generally limit patient compliance and effectiveness, it is imperative that treatment options are chosen based on the cause, effectively [6]. Surgical procedures such as endometrial ablation, myomectomy and hysterectomy can be applied when hormonal and non-hormonal medical treatment options do not respond or are insufficient [7]. In general, 80% of women receiving treatment for abnormal uterine bleeding do not have an anatomical pathology; therefore, the uterus was found to be anatomically normal in one third of the women who underwent hysterectomy.…”
Section: Early Onlinementioning
confidence: 99%
“…However, since the side effects that develop during treatment generally limit patient compliance and effectiveness, it is imperative that treatment options are chosen based on the cause, effectively [6]. Surgical procedures such as endometrial ablation, myomectomy and hysterectomy can be applied when hormonal and non-hormonal medical treatment options do not respond or are insufficient [7]. In general, 80% of women receiving treatment for abnormal uterine bleeding do not have an anatomical pathology; therefore, the uterus was found to be anatomically normal in one third of the women who underwent hysterectomy.…”
Section: Early Onlinementioning
confidence: 99%
“…There is some concern regarding the risk for decreased ovarian function following UAE due to misembolization of the ovarian artery—an adverse event that now appears to be less common than initially thought 28 . Recent meta‐analyses have suggested no appreciable impact on ovarian reserve as measured by mean serum concentrations of anti‐Müllerian and follicle‐stimulating hormones 29,30 . The issues regarding UAE and both fertility and future pregnancy remain the prevailing concerns about the propriety of this procedure in women wishing to conceive in the future 31–33 …”
Section: Procedural Interventionsmentioning
confidence: 99%
“…Indeed, there is no medical rationale for any discontinuation—a circumstance that should allow clinicians to use these products in a continuous fashion. The ring has the advantage that the dose of systemic estrogen is half that of the pill or patch 30 . Combined hormonal contraceptives are often well tolerated; however, there are several clinical circumstances, such as existing vascular disease, smoking over the age of 35, or a previous estrogen‐responsive malignancy, where their use is relatively or absolutely contraindicated 60…”
Section: Medical Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Sirkeci et al 5 report on the FEMME randomized controlled trial to determine treatment options for women with uterine fibroids wishing to avoid hysterectomy. The study randomized 254 women to either uterine artery embolization (UAE) or myomectomy treatment, and found that quality of life was greater in the myomectomy group at 2 years, but neither menstrual blood loss nor markers of ovarian function differed between the groups.…”
mentioning
confidence: 99%